Mobile and ubiquitous systems: computing, networking, and services : 10th International Conference, MOBIQUITOUS 2013, Tokyo, Japan, December 2-4, 2013, Revised Selected Papers - Cheng, Zixue; Guo, Song; Stojmenovic, Ivan (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th International ICST Conference on Mobile and Ubiquitous Systems: Computing, Networking, and Services, MobiQuitous 2013, held in Tokyo, Japan, in December 2013. The 67 revised full papers presented were carefully reviewed and selected from 141 submissions. The papers and 2 invited talks cover a wide range of topics such as mobile applications, social networks, networking, data management and services.